2020
DOI: 10.1155/2020/4689798
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Decitabine Assists Human Umbilical Cord-Derived Mesenchymal Stem Cells in ProtectingβCells via the Modulation of the Macrophage Phenotype in Type 2 Diabetic Mice

Abstract: Background. Progressive β-cell dysfunction, a major characteristic of type 2 diabetes (T2D), is closely related to the infiltration of inflammatory macrophages within islets. Mesenchymal stem cells (MSCs) have been identified to alleviate β-cell dysfunction by modulating macrophage phenotype in T2D, but the restoration of β-cells by a single MSC infusion is relatively transient. Decitabine (DAC) has been reported to polarize macrophages towards the anti-inflammatory phenotype at low doses. We therefore investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Macrophages are vital for the immune response and switch between two phenotypes in order to fulfill their role [17,18] . M1 macrophages secrete high levels of proinflammatory cytokines (TNF-α, IL-6, IL-1β) and produce reactive oxygen species through activation of iNOS.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages are vital for the immune response and switch between two phenotypes in order to fulfill their role [17,18] . M1 macrophages secrete high levels of proinflammatory cytokines (TNF-α, IL-6, IL-1β) and produce reactive oxygen species through activation of iNOS.…”
Section: Resultsmentioning
confidence: 99%
“…As a regular demethylation regimen for myelodysplastic syndrome, DAC has been found to be advantageous in multiple myeloproliferative diseases such as Hodgkin lymphoma and acute myelogenous leukemia by regulating immune response. 39 , 40 Recently, growing evidence has indicated that low‐dose DAC‐induced M2 macrophage polarization could ameliorate acute lune injury 41 and atherosclerosis, 42 implying the potential role of DAC on immunological disorders. The aberrant DNA methylation has been found to participate in the pathophysiology of ITP, 43 targeting the DNA methylation could be used as a new treatment for ITP.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 secreted by HUC-MSCs synergistically regulates macrophage polarisation with IL-6 71 . Additionally, low-dose decitabine may prolong the antidiabetic effects of MSCs and promote sustainable β-cell recovery by polarising macrophages to the M2 phenotype 72 . Overall, HUC-MSCs can reduce islet β-cell inflammation by polarising macrophages to the M2 anti-inflammatory phenotype, thereby alleviating islet dysfunction in patients with DM.…”
Section: Possible Mechanisms Of Huc-mscs For Dm Treatmentmentioning
confidence: 99%